Upaya Normatif Dan Sosiologis Mewujudkan Keluarga Sakinah Pada Pasangan Long Distance Marriage - Khiyaroh, Khiyaroh; Imamudin, Fauzi (Universitas Cokroaminoto Yogyakarta, 2024)
Long distance marriage (LDM) is a condition in which married couples choose distance and time constraints to meet each other. The impact of these obstacles causes a fairly short meeting time. Short meetings make families have less time to be together. In long distance marriage, there are several obstacles faced such as distance and communication and of course in carrying out obligations and rights in marriage. This research is a field research where the author will interview two respondents who are undergoing a long distance marriage because their husbands work outside the city. The author will analyze with two theories, namely Max Weber's theory of social action and maqashid Shari'ah. The results of the study found that the motive of husbands who work outside the city is purely to make a living for the family. And in the perspective of maqashid, there are three main things that are protected, namely hifdzu din, hifdzu maal and hifdzu nasl. So it can be said that families who choose to undergo a long distance marriage can form a sakinah family. This can be seen from the rights and obligations of husband and wife that are fulfilled.